2009
DOI: 10.1093/ejechocard/jen339
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of left atrial appendage function with transthoracic tissue Doppler echocardiography

Abstract: Acquiring and quantifying LAA A(M) contraction velocity is feasible on TTE in a high percentage of patients and correlates with TEE. LAA A(M) was lower in AF compared with sinus rhythm, with spontaneous echo contrast compared to without spontaneous echo contrast, and in AF patients with a history of stroke or TIA. Those with LAA thrombus had the lowest LAA A(M) velocities. LAA A(M) is a novel functional parameter that may prove useful for risk stratification of AF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
60
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(63 citation statements)
references
References 30 publications
3
60
0
Order By: Relevance
“…Several studies were attempted to resolve the problem, such as that performed by Tamura et al [13] and Uretsky et al [14]. They suggested that Doppler tissue velocity of the LAA tip measured from the TTE was an independent predictor of LAA thrombus formation and may be useful for risk stratification of AF.…”
Section: La S/sr In Prediction Of Laa Stasismentioning
confidence: 99%
“…Several studies were attempted to resolve the problem, such as that performed by Tamura et al [13] and Uretsky et al [14]. They suggested that Doppler tissue velocity of the LAA tip measured from the TTE was an independent predictor of LAA thrombus formation and may be useful for risk stratification of AF.…”
Section: La S/sr In Prediction Of Laa Stasismentioning
confidence: 99%
“…Second tissue harmonic mode allows better visualisation of LAA, providing planimetric assessment of LAA area and fractional area change almost in all patients, as well as pulsed wave Doppler assessment of flow velocity (Fig. 4) [6,18,19,51,52]. TTE parameters of LAA contractility closely correlated with those measured by TEE.…”
Section: Transthoracic Echocardiographymentioning
confidence: 69%
“…Recently, new evidence has appeared regarding the use of M-mode and pulsed wave tissue Doppler imaging (TDI) for the study of LAA [2,[18][19][20]. LAA contractility in both AF and SR can be studied directly through the assessment of fractional area change, ejection fraction, and fractional shortening by means of B-and M-mode echocardiography.…”
Section: Left Atrial Appendagementioning
confidence: 99%
“…In contrast, the superior temporal and spatial resolution constitutes a potential advantage of TEE. Furthermore, transthoracic echocardiography (TTE) was recently introduced as another non-invasive alternative to TEE for the assessment of LAA emptying [7]. …”
Section: Discussionmentioning
confidence: 99%
“…However, TEE is invasive, requires sedation and is associated with the potential risk of complications in the upper gastro-intestinal-tract [6]. Therefore growing interest has been recently paid to non-invasive techniques for the assessment of LAA emptying [7]. …”
Section: Introductionmentioning
confidence: 99%